Modification on the catalytic properties of CuCe mixed metal oxides catalyst for removal of COx: a review / Muhammad Fadli Hanafi Abdul Rais - Abdul Rais, Muhammad Fadli Hanafi (2022)
Carbon monoxide (CO) is a widely distributed byproduct of incomplete combustion of carbon-containing fuels. The amount of oxygen that can be transported to essential organs like the heart and brain through the bloodstream is limited when breathing CO-rich air. At very high levels of CO, which are achievable indoors or in other confined spaces, it can cause dizziness, confusion, coma, and death. To remove COx, several ways for removing COx have been investigated, one of which is the selective catalytic process. The modification on the catalytic properties such as the effect of calcination temperature of CuCe catalyst, the effect of chemical doping and the effect of impregnation method very important because it will change the performance of CuCe mixed metal catalyst for removal of COx. Many journals have been read and analyse to know which method is the best for modified catalytic properties on CuCe mixed metal catalyst. In conclusion, the effect of chemical doping on CuCe for removal of COx is the best technique than effect of calcination temperature and effect of impregnation method.